NADPH oxidase p22phox gene expression in ulcerative colitis - Bülbül, Neşe; Pala, Elif; İğci, Yusuf Ziya; Göğebakan, Bülent; Öztuzcu, Serdar; Cengiz, Beyhan; Bayraktar, Recep; Dağ, Muhammet Sait; Aydınlı, Musa (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, which catalyzes the formation of reactive oxygen species (ROS) in phagocytic cells, has five subunits: p67phox (“phox”refers to “phagocyte oxidase”), p47phox, p40phox, p22phox, and gp91phox (catalytic subunit). Oxidative stress resulting from the accumulation of ROS and/or defective removal of ROS by antioxidants has detrimental effects on cellular functions and may contribute to chronic inflammation. Disruption of the colonic mucosa due to the dysregulation of antioxidants or transformation enzymes may play a role in the pathogenesis of ulcerative colitis (UC) and influence the clinical features of this disease. In this study, we examined the expression of the gene encoding NADPH oxidase subunit p22phox cytochrome b-245, alphapolypeptidein the colonic mucosa to test its possible contribution in the pathogenesis of UC. Materials and Methods: Expression levels of mRNA in the inflamed and non-inflamed colonic mucosa (determined using colonoscopy)of 22 patients with UC and in the normal mucosa of 22 healthy controls were analyzed using real-time polymerase chain reaction. Results: Expression levels of mRNA were not significantly different between patients with inflamed and non-inflamed colonic mucosa (p>0.05) and betweenpatients with inflamed colonicmucosa and healthy controls (p>0.05). Conclusion: Although our data suggest that expression of the gene encoding p22phox is not associated with chronic inflammation in patients with UC, other mechanisms can affect oxidative stress in these patients.